Solid Phase–Enhanced Photothermal Lensing with Mesoporous Polymethacrylate Matrices for Optical-Sensing Chemical Analysis. Issue 7 (July 2013) - Nedosekin, Dmitry A.; Saranchina, Nadezhda V.; Sukhanov, Aleksey V.; Gavrilenko, Nataliya A.; Mikheev, Ivan V.; Proskurnin, Mikhail A.
Procedures for the photothermal lens determination of metals and organic compounds, on the basis of solid-phase mesoporous optical-sensing materials (polymethacrylate [PMA]) matrices with immobilized reagents, were developed. These procedures combine (i) selective and efficient preconcentration of trace substances to be analyzed in specially designed and synthesized transparent mesoporous PMA plates; (ii) sensitive determination with the reliable and traceable photometric reactions previously developed for classical spectrophotometry; and (iii) the sensitivity enhancement of photothermal lens detection in polymers, which provides at least a ten-fold increase in sensitivity compared with solutions due to polymer thermo-optical properties (solid phase–enhanced thermal lensing). It is shown that the overall sensitivity of photothermal lens measurements in PMA matrices is two orders higher than photometric absorbance measurements for the same excitation source power, which is in good agreement with the expected theoretical sensitivity. Changes in the preparation of transparent PMA plates and analytical procedures for photothermal measurements compared with spectrophotometry are discussed. PMA matrices modified with various analytical reagents were applied to trace determination of Hg(II), Fe(II), Ag(I), Cu(II), and ascorbic acid, with subnanomolar to nanomolar limits of detection.